2015
DOI: 10.1016/j.jagp.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic Exposure During Rehabilitation: Cognitive and Physical Function Outcomes in Patients with Delirium Superimposed on Dementia

Abstract: Objectives We examined the association between anticholinergic medication exposure and subsequent cognitive and physical function in patients with delirium superimposed on dementia during rehabilitation. We also examined length of stay and discharge disposition by anticholinergic medication exposure. Design In this secondary analysis we used control group data from an ongoing randomized clinical trial. Setting/Participants Participants with delirium and dementia were enrolled at admission to post-acute car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
(46 reference statements)
1
19
0
Order By: Relevance
“…Dementia and age are widely recognized risk factors for delirium in older hospitalized patients, and our findings confirm previous results in other settings [13, 19, 27]. On the other hand, although polypharmacy in older hospitalized patients is associated with delirium in many studies [10, 28, 29], our study did not confirm this association. This could be consistent with data by Moorey et al [30], showing that the number of prescribed drugs inversely correlated with age.…”
Section: Discussionsupporting
confidence: 50%
“…Dementia and age are widely recognized risk factors for delirium in older hospitalized patients, and our findings confirm previous results in other settings [13, 19, 27]. On the other hand, although polypharmacy in older hospitalized patients is associated with delirium in many studies [10, 28, 29], our study did not confirm this association. This could be consistent with data by Moorey et al [30], showing that the number of prescribed drugs inversely correlated with age.…”
Section: Discussionsupporting
confidence: 50%
“…An interaction was found between ApoE4 carriers and anticholinergic medications with users having the lowest cognitive scores. Irrespective of ApoE4 status, drugs with high anticholinergic properties were associated with cognitive and physical decline (Jamsen et al, 2016; Kolanowski et al, 2015; Lanctot et al, 2014; Risacher et al, 2016; Uusvaara et al, 2009). Methods for measuring medication burden varied significantly between studies making it difficult compare study results.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, no previous studies investigated the possible association between anticholinergic drug use and clinical outcomes in acutely ill hospitalized older patients with delirium. Recently, Kolanowski et al (2015) found that the use of anticholinergic drugs according to the ACB was associated with prolonged LOS and reduced physical function, but not with discharge disposition in older persons with delirium who resided in a postacute care facility. In contrast to our study, their sample size was relatively small, all participants had dementia, were not acutely ill, and in the vast majority delirium was resolving.…”
Section: Discussionmentioning
confidence: 99%